Gait initiation and lateral wedge insole for individuals with early knee osteoarthritis. (December 2020) - Esfandiari, Elham; Sanjari, Mohammad Ali; Jamshidi, Ali Ashraf; Kamyab, Mojtaba; Yazdi, Hamid Reza
Abstract: Background: People with knee osteoarthritis are at higher risk of postural deficits and locomotor adaptations which could be manifested in transient tasks like gait initiation. To better understand the effect of early knee osteoarthritis on gait initiation, we measured the gait initiation in two groups of early knee osteoarthritis and healthy age-matched controls and assessed the effect of lateral wedge insole in knee osteoarthritis group. Methods: Twenty-one individuals with early knee osteoarthritis, mean (SD) age = 53.1 (7.4, years), and 19 age- and sex-matched asymptomatic healthy individuals, mean (SD) age = 47.5 (11.2, years), participated. Centre of pressure trajectories were used to quantify the two phases of gait initiation in barefoot condition: anticipatory postural adjustment, and locomotor phase. The immediate and four-week effect of lateral wedge insole and shod condition were also compared for individuals in knee osteoarthritis group. Findings: Longer duration of anticipatory postural adjustment phase ( P = 0.046), locomotor phase ( P = 0.049), and total duration of gait initiation ( P = 0.035) with lower length and velocity of the center of pressure trajectories in anticipatory postural adjustment phase ( P = 0.002, and 0.008, respectively) were observed in knee osteoarthritis group compared to controls. Lateral wedge insole could increase the length and velocity of the centre of pressure in locomotor phase compared to barefoot condition ( P = 0.001, and 0.002, respectively). Interpretation: Our study outlined that people with early knee osteoarthritis adopt different gait initiation strategies mainly in postural preparation phase. The potential effect of lateral wedge insole was shown with better performance of the locomotor phase. Clinical trial registry number: IRCT2016060628310N1. Graphical abstract: Unlabelled Image Highlights: Early knee osteoarthritis is associated with longer gait initiation cycle. Anticipatory postural adjustment phase is longer in early knee osteoarthritis. Bipedal standing phase is longer in early knee osteoarthritis. Lateral wedge insole can improve locomotor phase in knee osteoarthritis.